Development and Analysis Validation Instrument Critical Thinking Heat Concept (CTHT) Using Rash Model - Siska Aryani; Hera Novia; Andhy Setiawan (Postgraduate, University of Mataram, 2024)
This research aims to design and determine the validity and reliability of critical thinking skills instruments related to heat concepts using the Rasch model. This research uses 4D research and development methods. The research subjects or validation trials were 193 Depok City High School students majoring in Mathematics and Natural Sciences who had studied heat concepts and content validation was carried out with six expert lecturers. Content validity data analysis used Aiken V Microsoft Excel calculations with a validity limit value of < 0.78 and construct validity and reliability used the Rasch model. The results of data analysis show that the content validity of the instrument is valid and suitable for use with several revisions and expert input, while the results of content validity show a validity level of 43.21% with all valid items in the fulfilled category, while the Pearson and item reliability values show a value of 0.62 is in the sufficient category and 0.92 is in the very special category. The results of the statistical analysis trial showed that the instrument was significant and became a benchmark for further research in the application of students' critical thinking skills in learning.